Video-Assisted Needle Core Biopsy in Children Affected by Neuroblastoma: A Novel Combined Technique - Avanzini, Stefano; Faticato, Maria Grazia; Sementa, Angela Rita; Granata, Claudio; Martucciello, Giuseppe; Pio, Luca; Prato, Alessio Pini; Garaventa, Alberto; Bisio, Giovanni; Montobbio, Giovanni; Buffa, Piero; Mattioli, Girolamo (European Journal of Pediatric Surgery, 2017)
Aim This study aims to evaluate the experience gained with video-assisted needle-core biopsy in patients affected by neuroblastoma (NB).Patient and Methods We retrospectively reviewed all the patients presenting at our center with a thoracic, abdominal, and/or pelvic NB who underwent biopsy between 2007 and 2014. Data on demographics, localization, and size of the tumor, image-defined risk factors involved in each case, technical details about biopsies performed, qualitative and quantitative adequacy of tumor sampling and histological diagnosis, postoperative details, and complications were recorded and analyzed.Results During the 7 years of our study 51 patients affected by NB underwent 55 biopsies. Our results focus on the 29 patients undergoing 32 video-assisted needle-core biopsies. The median age was 4 years with a median weight of 13.5 kg. Out of 29, 28 tumors were localized in the abdomen/pelvis compartment, whereas 1 patient presented with a thoracic mass. The median size of the tumors was 57 mm. A total of 28 patients had an adequate tissue sampling for complete tumor characterization. Biopsies were repeated twice in a patient. Three complications occurred in three patients.Conclusions The video-assisted needle-core biopsy combines minimally invasive surgery several advantages with the possibility to obtain multiple samples in different regions with minimal tumor exposition and low complication rate.
Keywords: neuroblastoma; biopsy; minimally invasive surgery; children; surgery